A flexicon without words - Melanie J. Bell; R. Harald Baayen (The Mental Lexicon, 2026)
Abstract This study investigates how the concept of morphological transcendence ( Libben, 2010 , 2014 ) is manifest across semantic, visual, and phonetic processing of English compounds. The theory of morphological transcendence proposes that constituents inside compounds take on position-specific meanings that differ from their meanings as independent words. We first assess this claim using the CAOSS model ( Marelli et al., 2017 ), which represents a compound as the sum of two transformed constituent semantic vectors that can be interpreted as transcended meanings. CAOSS provides a useful computational formalisation of this idea and captures aspects of semantic transparency within its training data. However, it generalises poorly to unseen compounds, highlighting the context sensitivity of compound interpretation and the limits of a single global mapping from constituent meanings to compound meanings. We next examine subliminal reading using a Discriminative Lexicon Model (DLM; Heitmeier et al., 2026 ). Because reading is incremental, early comprehension depends on the location of ocular fixation. We show that access to low frequency boundary trigrams allows the DLM to shift rapidly toward the compound meaning, an effect we term ocular transcendence. Predictors from the DLM model account well for lexical decision latencies, whereas predictors from the CAOSS model do not, suggesting that the two models capture different aspects of comprehension. Finally, we analyse the pitch contours of three-constituent compounds. We demonstrate that these contours transcend those of the constituents alone, providing evidence for an effect we term phonetic transcendence. Together, these findings support a view of the lexicon as a dynamic, context-sensitive system, aligning with Libben’s (2022) broader theoretical framework in which the mental lexicon is best understood as a flexicon.